Mengoptimalkan Kinerja Perusahaan: Apakah Dividen Memiliki Peran Moderasi? - Gymnastiar, Hamzah; Mukhibad, Hasan; Jayanto, Prabowo Yudo; Wahyuningrum, Indah Fajarini Sri (Business and Accounting Education Journal, 2025)
This study set out to investigate experimentally how capital structure, as influenced by dividend policy, affects business performance. The study's population consists of 113 Basic Consumer Sector Manufacturing Companies that were listed between 2019 and 2022 on the Indonesia Stock Exchange (IDX). Purposive sampling was applied in the sampling process, yielding a sample of 46 businesses and 162 units of analysis with imbalanced data. Using panel data regression analysis and Moderated Regression Analysis (MRA) with the aid of the STATA software, the approach combines descriptive and inferential analysis. The results showed that capital structure negatively affects firm performance. Furthermore, dividend policy in this study has a moderating role by strengthening the negative effect of capital structure on firm performance. This study makes a new contribution to the existing literature because it considers the moderating effect of dividend policy on firm performance.